Interpreting biomonitoring data - Nakayama, Shoji F. (2022)
Funding Information: The authors of this paper are members of the ISES i-HBM Working Group. The i-HBM is chaired by the National Institute of Environmental Health, Japan and co-chaired by Health Canada, and the group is comprised of an international assemblage with expertise in various aspects of biomonitoring (i-HBM members are co-authors of this paper or included in the Acknowledgments section). We would like to thank other Working Group members for their insights: Jillian Ashley-Martin, Ana Canas, André Conrad, Scott Hancock, Carin Huset, Tomohiko Isobe, Jung-Taek Kwon, Jueun Lee, Marc A. Nascarella, Andy Nong, Susana Pedraza-Diaz, Eva Sugeng, Natalie von Götz, Jiyoung Yoo. Publisher Copyright: © 2022